An Introduction to the Finite Element Method - Reddy (J N) (2006)
Finite Element Analysis
43820a.jpg;43820b.jpg;43820c.jpg;43820d.jpg;43820d.jpg;43820e.jpg;43820f.jpg;43820g.jpg
22.5
Keywords: Finite Element Analysis